PEMETAAN JALUR DAN TINGGALAN PERKERETAAPIAN MASA KOLONIAL BELANDA DI WILAYAH CIREBON TIMUR - Iwan Hermawan; Revi Mainaki (Jurnal Sosioteknologi, 2019)
Cirebon is one of the regions in West Java Province with a coastal landcape, its strategic location and fertile land makes Cirebon rich in agricultural resources. These conditions encouraged the Dutch Government to exploit and occupy in Cirebon. The relatively abundant exploitation of commodities has led to the establishment of efficient transportation facilities for transporting agricultural products. Railroad is an efficient transportation transportation technology that at that time developed, so railroad lines, stations and stops were built with all the facilities. The first development was the Semarang - Cirebon route with the tram class of 1897 and continued to experience development. Through a qualitative approach with a descriptive explorative research method this research seeks to map and identify railroad relics in the Cirebon Region, based on Geographic Information System technology (GIS) to obtain historical social information on the development of the Cirebon Region during the Dutch Colonial period. Data was collected through observation by tracing rail tracks so that railroad relics were found in the form of railroad tracks, stations and stops that were still functioning or those that were no longer active. The tracing data was strengthened with literature studies, literature studies and documentation studies and then analyzed with the Geographic Information System so that a map of the railroad distribution was obtained and described in written form. The results of the study found railroad relics in the form of former railroad tracks, former station buildings and former stops with various supporting facilities including the former buildings of Mundu Station, Warudurur, Kanci, Sindanglaut, Karangsuwung, Jatiseeng, Ciledug, Losari and Babakan. Then stop at Jatipiring, Cibogo, Waled, Luwunggajah, and Titik Simpang Bedilan. The remains are scattered along the former railroad tracks, both those that are still functioning and those that are no longer active.